High-Intensity Interval Training in Female Adolescents with Moderate or Severe Obesity - Ghazi Racil; Luca Russo; Gian Mario Migliaccio; Paola Signorelli; Alin Larion; Johnny Padulo; Mohamed Chedly Jlid (MDPI AG, 2023)
This study aimed to investigate the impact of moderate- or high-intensity interval training (MIIT or HIIT) on anthropometric and biological measurements in four groups of females with obesity. Fifty-seven participants were divided into a moderate obesity group (MOG, n = 29) and a severe obesity group (SOG, n = 28). Two sub-groups were established to practice HIIT and MIIT programs (SOGHI, n = 14; SOGMI, n = 14; MOGHI, n = 14; MOGMI, n = 15). During the training sessions, each group performed two sets of 4 × 1 min intervals on a cycle ergometer. The intervals were conducted at 65% and 85% of the heart rate reserve (HRR) for MIIT and HIIT, respectively. Between each repetition, there was an active recovery phase at 50% HRR, and, between sets, there was a 4 min period of free pedaling. All groups significantly improved their anthropometric data, while only MOGHI and SOGHI significantly improved their lean body mass (LBM) and blood lactate (BL), with p ˂ 0.05; the higher percentage of change in blood insulin levels (−25.49 and −25.34) and the homeostasis model assessment of the insulin resistance index (−31.42 and −28.88) were noted. Only MOGHI showed improvements in growth hormone (GH) and blood glucose (p < 0.05), which were negatively correlated with body fat percentage (r = −0.76 and r = −0.72) and waist circumference (r = −0.77 and r = −0.82), respectively. We may conclude that HIIT was an effective method of managing anthropometric and biological parameters, as confirmed by the pronounced body fat reduction in the moderate obesity group.